Nonsurgical root canal treatment of an Oehlers type IIIa maxillary central incisor with dens invaginatus: a case report - Inoue, Ayumi; Kawanishi, Yuzo; Okamoto, Motoki; Hayashi, Mikako (Frontiers in Dental Medicine, 2024)
Dens invaginatus has a complex anatomy, making endodontic treatment challenging. We report the case of a 11-year-old girl who presented with radiolucency at the apex of the maxillary central incisor; she was diagnosed with symptomatic apical periodontitis. Cone-beam computed tomography (CBCT) revealed dens invaginatus. The invagination and root canal were observed using a dental operating microscope, and nonsurgical root canal treatment was performed. The invagination was connected to the periodontal tissue, and the tooth was classified as Oehlers type IIIa. Root canal preparations were performed using NiTi files and an ultrasonic device. A calcium hydroxide paste was used as an intracanal dressing. The root canal was filled using a single-cone hydraulic condensation technique with a highly fluid calcium silicate-based sealer. At the 2-year follow-up, no clinical symptoms were observed, and CBCT images revealed no radiographic lesions. Nonsurgical endodontic treatment using CBCT imaging, dental microscope, effective cleaning systems, and a highly fluid sealer facilitated the successful treatment of apical periodontitis attributed to dens invaginatus. The single-cone hydraulic condensation technique using a bio-ceramic sealer is considered effective even in cases with a complex morphology and open apex.